STRATIGRAPHY AND PETROLEUM SYSTEMS OF THE PALAEOZOIC (PRE‐KHUFF) SUCCESSION, QATAR. (October 2016) - Al‐Saad, H.; Sadooni, F.N.
Abstract : A thickness of more than 1500m of Palaeozoic (pre‐Khuff) siliciclastic strata were encountered in three deep wells (Matbakh A, and Dukhan A and B) drilled in the State of Qatar. These sedimentary rocks have no formal entries in the Qatari Geologic Lexicon and were not included in sequence stratigraphic schemes of the Arabian Plate region. The rocks are investigated here using cores, well logs and other materials. The pre‐Khuff succession has been divided from the base up into the Qasim, Qusaiba, Sharawra, Tawil and Unayzah Formations based on age, stratigraphic status, lithology, sedimentary structures and correlation with the Saudi stratigraphic nomenclature. The succession is divided into a series of third‐order sequences based on the identification of the principal maximum flooding surfaces. Deposition is interpreted to have occurred in a wide range of environments ranging from fluvial to shallow‐marine but with the absence of the glacial facies which are prevalent in the equivalent Saudi section. Core and log analyses indicate that the Qusaiba Formation represents an important source rock which became mature for hydrocarbon generation during the Late Permian; it generated oil until the Late Jurassic and then began to expel gas and condensates, continuing until the present day. Both the Qasim and Sharawra Formations may include potential reservoir rocks which merit further study. The new nomenclature reported here will assist with the understanding of the Palaeozoic palaeogeography across the Arabian Peninsula and will help to delineate reservoir rocks in the Qatari Palaeozoic succession.